A comparative study of the vocational interests of black and white school-leaving boys in South Africa - Breger, Richard Allen (Rhodes University, Faculty of Humanities, Department of Psychology, 1976)
This is an exploratory study to compare the vocational interests of Black and White school-leaving boys in South Africa. The aim of the study is, first, to test the hypothesis that the samples hold similar stereotypes of vocations and that they structure interest fields in a similar way; and, second. to test the hypothesis that the vocational interests of the samples are different. The samples comprise four hundred and ten matriculants from schools in Johannesburg and Soweto. The methodological requirements for conducting cross-cultural research are adhered to as far is practically possible. The main findings provide general support for the hypotheses. It is found that the Black and White samples have similar vocational stereotypes and that they structure interest fields similarly, and in a way which closely approximates the reported structures characteristically found in Western culture. The Black and White samples differ in their vocational interests, although there are also similarities.
Keywords: Vocational interests -- South Africa; Vocational interests -- Cross-cultural studies